Prediction of Land Cover Model for Central Ambon City in 2041 Using the Cellular Automata Markov Chains Method - Heinrich Rakuasa; Daniel A Sihasale; Glendy Somae; Philia Christi Latue (Department of Geophysical Engineering, Faculty of Engineering, University of Lampung, 2023)
The Ambon city center area based on the 2021-2041 RDTR is a center of economic, educational and cultural activities, this makes economic and population growth focused in this region. This also triggers the arrival of residents from other areas to Ambon City and will have an impact on increasing the provision of land for settlements. This condition is expected to trigger land conversion in this area. This study aims to analyze land cover changes in Ambon City in 2001, 2011, 2021 and predict land cover in 2041. This study uses Cellular Automata Markov Chains modeling to predict land cover in the central area of Ambon City in 2041. The results show that the type of built-up land cover and open land continued to increase in area, while agricultural and non-agricultural areas continued to experience a decrease in area and water bodies did not experience a decrease in area. The results of this study are expected to be used as a reference in managing the development of sustainable residential areas and as an effort to arrange land use in the Ambon City center area in the future based on ecological aspects.